EKSPLORASI PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MOTIVASI BELAJAR SISWA PADA PENDIDIKAN DASAR - Nailan, Akhmaliah Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The aim of this research is to identify the teaching proficiency of educators in class IV MIN Bandung in integrated thematic learning, student learning motivation in class IV MIN Bandung in integrated thematic learning and, the connection between teachers' pedagogical skills and students' motivation in integrated thematic education in class IV MIN. Bandung. quantitative. The number of respondents used is 75 students of class IV MIN Bandung. Questionnaires and documentation are data collection techniques using a quantitative research approach in the form of correlational methods. The showed that the teacher's pedagogic competence in integrated thematic learning in class IV MIN Bandung had a percentage of 65.33% which was in the high category and the average amount was 57.49 of the maximum average of 80. The motivation of students in integrated thematic learning for class IV at MIN Bandung falls into the very high category, with 41.34% achieving this level and an average score of 70.35 out of a maximum possible average of 92. The correlation between teachers' pedagogical competence and students' learning motivation in integrated thematic learning for class IV at MIN Bandung was found to be 0.630, indicating a high level of association. The teacher"™s pedagogic participation affects srudents"™ learning motivation by 40%.